A Mediterranean gap in the national canon?: Paul Carpita’s anti-colonial cinema between militant amateurism and New Wave - Winkler, Daniel (Studies in French cinema, 2017)
A new Marseille cinema, focusing on the city’s everyday culture, emerged in the 1980s with directors such as René Allio and Robert Guédiguian. Even though some of their films received considerable recognition, an important part of the history of this cinematic representation has remained largely unaccounted for: the work of Paul Carpita (1922-2009). His films of the 1950s and 60s are strongly linked to the cultural history of the labour and peace movement. A former member of the Resistance, he created just after World War II Le Rendez-vous des quais/Meeting on the Docks(1953-55), a full-length film shot in the popular quarters of Marseille, thematising the dockers’ protest against the Indochina War. The film was censored before its release and only restored in the 1980s. This article situates the film within the regional and national French cinema of the post-war era, and analyses its hybrid aesthetics, comprising cinematic realism, militant cinema and amateur film. By referring to Carpita’s more intimate and reflexive short films, the article argues that his marginal status within French film history can be traced to the political and amateurish character of his films, but also to the fact that his artistic activity was located in Marseille, at the periphery of the national film scene and academia.
Gesehen am 21.12.2021